Meningkatkan Aktivitas, Motivasi Dan Keterampilan Menulis Simple Present Tense Menggunakan Model Lecture Pada Sekolah Dasar - Wanda Azizah; Ratna Purwanti (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the low activity, motivation and writing skills in English content Simple Present Tense. The purpose of this finding is to describe quality improvements through educator activities, analyzing student activities, learning motivation and students' writing skills. This study used Classroom Action Research (PTK) which was carried out in 3 meetings. The research subjects were the fifth grade students at SDN Sungai Miai 2 Banjarmasin totaling 25 students consisting of 11 male students and 14 female students. The data obtained is qualitative data through observing the activities of educators, students, learning motivation questionnaires and quantitative data so that students' writing skills are obtained through written tests individually and in groups. The benchmark for research success is that 80% of students obtain or exceed the specified KKM ≥75. Based on the data findings and results of this study, it can be concluded that learning using the LECTURE model (Problem Based Learning, Think Talk Write, and Picture and Picture) is able to provide an increase in students' activity, motivation and writing skills.